Review on Trust Building Algorithms in IoT Security - Wang, Haoxiang (Journal of ISMAC, 2022)
IoT security is a combination of physical device security and network security. The objective of the IoT security module is to hide the network from communication vulnerabilities between the transmitter module and the server. Also, the security algorithms are designed to protect the systems from software attacks and physical hardware attacks. The paper explores the ongoing advancements and research in the field of IoT security by analyzing the research limitations and issues of the existing models. The research gaps identified from the literature analysis explores the way where the research on IoT security must be narrowed. Moreover, this paper projects the evolution of security threats in the IoT network, along with the analysis of deep learning models in estimating such threats.